"It feels like home": Transgender youth in the Midwest and conceptualizations of community climate. Issue 6 (17th May 2020) - Paceley, Megan S.; Sattler, Patricia; Goffnett, Jacob; Jen, Sarah
Abstract: Community climate toward sexual and gender minority (SGM) youth is associated with higher rates of victimization and poorer health and wellbeing‐related outcomes such as depression and suicidal ideation. However, this field of research has underemphasized the experiences of transgender youth, particularly within the Midwestern context which is marked by vast rurality and characterized as sociopolitically conservative. Using qualitative and community‐based methods, this study identified factors that impact community climate from the perspective of transgender youth ( n = 19) in the Midwest and situated them within the Ecological Systems Theory (EST). Thematic analysis of interviews revealed four themes: resources, visibility, policies, and ideologies. Themes often crossed levels within the EST, indicating the complexity and interrelated nature of climate across local, regional, and national contexts. Implications for theory, research, and practice are discussed.